An Analytical Study of Racism in Two of Toni Morrison’s Novels - Sarah A. Khuder; Mohanad R. Safar (PROSPECTIVE RESEARCHES, 2023)
Toni Morrison is an incredible American novelist. In 1993, she received the Nobel Prize in Literature, only the eighth woman ever to do so, and the first black woman. Upon awarding the prize, the Swedish Academy described her as a writer “who, in novels characterized by visionary force and poetic import, gives life to an essential aspect of American reality.”[1]. Her novels bring to light the dim lives of slaves. She tackles the relations inside the African American society. Race, social class, slavery, and gender are the main themes in Morrison's novels. Whiteness in her novels is frightening the characters and preventing them from getting their own identity in the society. In this paper, her two novels The Bluest Eye and Beloved are tackled which shed light on the ideas of racism, gender and oppression of black people.